Ivy + Bean doomed to dance - Barrows, Annie (Barrows, Annie. Ivy + Bean, 2010)
Second-grade best friends Ivy and Bean beg for ballet lessons, then, when they are cast as squids in their first recital, scheme to find a way out of what seems to be boring, hard, and potentially embarrassing.